(untitled) (Al-Qamar, 2023)
Iqbal was a great philosopher of the 20th century. He presented philosophical ideas and theories. Iqbal has examined economic philosophy in the context of feudal economic system, capitalist system, Marxist and Islamic ideas. Iqbal’s economic thoughts are openly expressed in "ʻIlm-Ul-Iqtiesād” and his poetry. Iqbal wants Islamic economic system. Provision of universal human rights, equal distribution of wealth and equal opportunities for progress of mankind. Which can be achieved through Islamic economic system.